Epigenome-Metabolome-Epigenome signaling cascade in cell biological processes. (April 2022) - Li, Linpeng; Chen, Keshi; Wu, Yi; Xiang, Ge; Liu, Xingguo
Abstract: Cell fate determination as a fundamental question in cell biology has been extensively studied at different regulatory levels for many years. However, the mechanisms of multilevel regulation of cell fate determination remain unclear. Recently, we have proposed an Epigenome-Metabolome-Epigenome (E-M-E) signaling cascade model to describe the cross-over cooperation during mouse somatic cell reprogramming. In this review, we summarize the broad roles of E-M-E signaling cascade in different cell biological processes, including cell differentiation and dedifferentiation, cell specialization, cell proliferation, and cell pathologic processes. Precise E-M-E signaling cascades are critical in these cell biological processes, and it is of worth to explore each step of E-M-E signaling cascade. E-M-E signaling cascade model sheds light on and may open a window to explore the mechanisms of multilevel regulation of cell biological processes.